Press releases: from conventional to digital - Serajnik Sraka, Nada (Mednarodno inovativno poslovanje = Journal of Innovative Business and Management, 2019)
Digital technologies introduce major changes in all forms of communication, including in the field of written communication. Writing cmpetence is considered one of the most important competences needed by public relations practitioners in everyday work. We were interested in finding how web technologies influence the preparation of press releases, one of the most common communication tools, and at the same time the most common written public relations genres. and how the new approaches are reflected in the practice of public relations. We wanted to find out how digital technologies influence the process of preparing press releases, especially in terms of writing structure and layout. The research sample consisted of press releases of four governments (English, Canadian, German and Slovenian), a total of 40, published by the governments in one month (March 2018).